The Biological Characteristics of Novel H5N6 Highly Pathogenic Avian Influenza Virus and Its Pathogenesis in Ducks - Huang, Jianni; Wu, Siyu; Wu, Wenbo; Liang, Yiwen; Zhuang, Haibin; Ye, Zhiyu; Qu, Xiaoyun; Liao, Ming; Jiao, Peirong (Frontiers in Microbiology, 2021)
Clade 2.3.4.4 H5Nx highly pathogenic avian influenza viruses (AIVs) have caused outbreaks in poultry in the world. Some of these viruses acquired internal genes from other subtype AIVs such as H9, H6 for the generation of novel reassortant viruses and continually circulated in poultry. Here, we applied a duck-origin virus DK87 and a chicken-origin virus CK66 to assess the biological characteristics of novel reassortant H5N6 HPAIVs and its pathogenesis in ducks. Genetic analysis indicated that the HA genes of the two H5N6 highly pathogenic avian influenza viruses (HPAIVs) were closely related to the H5 viruses of clade 2.3.4.4 circulating in Eastern Asia and classified into H5 AIV/Eastern Asia (EA)-like lineage. Their NA genes fell into Eurasian lineage had close relationship with those of H5N6 viruses circulating in China, Laos, Vietnam, Japan and Korea. All internal genes of DK87 were aggregated closely with H5 AIV/EA-like viruses. The internal genes (PB1, PA, NP, M, and NS) of CK66 were derived from H9N2 AIV/SH98-like viruses and the PB2 were derived from H5 AIV/EA-like viruses. These results indicate that clade 2.3.4.4 H5N6 AIVs have continually evolved and recombined with the H9N2 viruses circulating in Southern China. Pathogenicity test showed that the two viruses displayed a broader tissue distribution in ducks and caused no clinical signs. These results indicated that ducks were permissive for the replication of the chicken-origin reassortant virus CK66 without prior adaptation, but the duck-origin virus DK87-inoculated ducks showed significantly higher viral titers in some organs than the CK66-inoculated ducks at 5DPI. The recovery of viruses from oropharyngea and cloacal swabs of contacted ducks indicated that they transmitted in native ducks by direct contact. qRT-PCR results revealed that the immune-relative genes (PRRs, IFNs, Mx-1, IL-6 and IL-8) in the lungs of inoculated ducks were expressed regardless of virus origin, but the expression of these genes were significantly higher in response to infection with the DK87 virus compared to the CK66 virus at 3 DPI. Overall, we should provide further insights into how clade 2.3.4.4 H5N6 AIVs undergo genetic and pathogenic variations to prevent outbreaks of this disease.